Ответ:
18
Объяснение:
[tex]x^{2}[/tex] - 5х + 2х - 10 - ([tex]x^{2}[/tex] - 7х + 4х -28 = [tex]x^{2}[/tex] - 3х - 10 - [tex]x^{2}[/tex] + 7х - 4х + 28 = 28 - 10 = 18
[tex]x^{2} -x^{2} =0[/tex]
7х - 3х - 4х = 0
[tex]\displaystyle\bf\\(x-5)(x+2)-(x-7)(x+4)=\\\\=x\cdot x+x\cdot 2-5\cdot x-5\cdot 2-(x\cdot x+x\cdot 4-7\cdot x-7\cdot 4)=\\\\=x^{2} +2x-5x-10-x^{2} -4x+7x+28=\\\\=\underbrace{(x^{2} -x^{2} )}_{0}+\underbrace{(2x-5x-4x+7x)}_{0}+(28-10)=18\\\\Otvet \ : \ 18[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
18
Объяснение:
[tex]x^{2}[/tex] - 5х + 2х - 10 - ([tex]x^{2}[/tex] - 7х + 4х -28 = [tex]x^{2}[/tex] - 3х - 10 - [tex]x^{2}[/tex] + 7х - 4х + 28 = 28 - 10 = 18
[tex]x^{2} -x^{2} =0[/tex]
7х - 3х - 4х = 0
[tex]\displaystyle\bf\\(x-5)(x+2)-(x-7)(x+4)=\\\\=x\cdot x+x\cdot 2-5\cdot x-5\cdot 2-(x\cdot x+x\cdot 4-7\cdot x-7\cdot 4)=\\\\=x^{2} +2x-5x-10-x^{2} -4x+7x+28=\\\\=\underbrace{(x^{2} -x^{2} )}_{0}+\underbrace{(2x-5x-4x+7x)}_{0}+(28-10)=18\\\\Otvet \ : \ 18[/tex]